The association between various indices of obesity and severity of atherosclerosis in adults in the north of Iran. Issue 50 (December 2016) - Salari, Arsalan; Shakiba, Maryam; Mahdavi-Roshan, Marjan; Gholipour, Mahboobeh; Naghshbandi, Moona; Rajabi, Ramin
Abstract : Abstract: Recent observational studies have reported controversial results for the association between different anthropometric indices of obesity and severity of atherosclerosis. The aim of the current study is to determine the associations between anthropometric indices with severity of atherosclerosis in adult population in north of Iran. The cross-sectional study was performed on 610 participants, who were admitted to a hospital for elective angiographyin Rasht, Iran, Anthropometric indices, including waist circumference (WC), waist-to-height ratio (WHtR), conicity index (CI), body mass index (BMI), and hematological factors, were measured using the standard methods. According to angiography reports, severity of atherosclerosis was determined. Sixty-two percent of participants had moderate to severe atherosclerosis. According to BMI, 44% were overweight and 25.8% were obese. Based on WHtR and WC, 90%, and 57% were obese, respectively. The prevalence of moderate to severe atherosclerosis in centrally obese women was significantly higher than in centrally nonobese women (52% vs 28% P  = 0.02). According to multivariate adjustment analysis, age, sex, systolic blood pressure, hemoglobin A1c, uric acid, and triglyceride were independently associated with severity of atherosclerosis. BMI, WC, CI, and WHtR had no significant association with severity of atherosclerosis. Our findings showed that anthropometric indices reflective of general and abdominal obesity were not independently related to the severity of atherosclerosis in adults, in northern Iran.